Role of blood Krebs von Lungen-6 in predicting acute exacerbation in patients with idiopathic pulmonary fibrosis - Eun Jun Choe; Ji Hoon Jang; Jin Han Park; So Young Jung; Minyoung Her; Jae Ha Lee (PLoS ONE, 2025)
Background This study evaluated the role of blood Krebs von den Lungen-6 (KL-6) in predicting acute exacerbation (AE) in patients with idiopathic pulmonary fibrosis (IPF). Methods From April 2018 to March 2023, clinical data of 233 IPF patients with baseline and follow-up KL-6 values at Haeundae Paik Hospital were retrospectively analyzed. AE was defined following the criteria proposed by Collard et al. in 2016. Results The mean age was 71.8 years; 79% were male. During follow-up (median: 18.7 months), 33 (14.2%) patients experienced AE. Throughout the entire period from baseline, KL-6 values were higher in the AE group compared to the non-AE group (P < 0.001), and the patterns of change over time also showed significant differences between both groups (P < 0.001). The KL-6 values in the post-exacerbation phase were higher than those in the pre-exacerbation phase among the AE group (P = 0.004). The AE group showed lower 1-year (86.4% vs. 95.9%) and 3-year (50.2% vs. 91.4%) survival rates compared to the non-AE group (P < 0.001). The occurrence of AE (hazard ratio (HR) 74.09, 95% confidence interval (CI) 31.97–171.7, P < 0.001) and higher lactate dehydrogenase (HR 1.02, 95% CI: 1.01–1.02, P < 0.001) were independently associated with mortality in patients with IPF Conclusions Our data suggest that the trend in changes in KL-6 values may be utilized as a tool for predicting AE-IPF. Further research is needed to establish the clinical significance of changes in KL-6 for predicting AE-IPF and to validate the cut-off values for prediction.